Formulação posicional não linear utilizando viscoelasticidade para análise de estruturas treliçadas - João Marcos Guimarães Rabelo (2015)
This master's thesis deals of the study of the viscoelastic behavior of creep of composite materials reinforced for fibers and of viability replacement of profiles/cables manufactures in steel for Glass Fiber Reinforced Plastics (GFRP). The motivations from study is to simulate the behavior in full-scale structures in time built in GFRP from uniaxial tests and thus be able to predict the evolution of the displacements of these structures considering the effects of creep. The idea of using this material for replacement of steel is due to competitive features such as low specific weight, resistance to corrosive agents, electrical and magnetic insulation and others. For this analysis, a formulation based on nodal positions is employed using the Zener Rheological model which is capable of describe the creep phenomenon at a temporal rate of deformation. This model is describe and implemented in the formulation to describe the calculating stress of Deformation Energy and then all the derivatives and the integrals are calculated and implemented for the calculation of the phenomenon. The program used is able to calculate structures such as transmission towers and cable-stayed bridges, thus, presented is an analysis in a cross arm transmission line tower (TLT) of electricity, where this cross arm is sized based in equations themselves for GFRP and analyzed in relation to specific weight obtained using this material, a reduction of 54,65%, as well as in relation to the viscoelastic behavior that showed an increase of 3,13% in the displacements the effects of creep. It presents also an example of a cable-stayed bridge cables GFRP to pay attention about the need for consideration of the creep phenomenon in tensioned structures subject to active loads for a long period of time and high stresses, in this case there was obtained higher displacements around 46,00% for the first 20,000 hours of service life of the structure.